Decoding plant resistance mechanism in pigeonpea (Cajanus cajan) against major insect pests: Decade of efforts and emerging directions - Dhanyakumar, Onkarappa; Ranjitha, Marigoudar; Yogendra, Kalenahalli; Revanayya, Gothe; Sharma, Hari C.; Taggar, Gaurav Kumar; Murugan, Marimuthu; Jagdish, Jaba (Elsevier, 2025)
Pigeonpea (Cajanus cajan (L.) Millsp.) is an important food and nutritional security crop, widely cultivated in the semi-arid regions of Asia and Sub-Saharan Africa. However, its productivity is hindered by various abiotic and biotic stress factors, including numerous insect pests that infest and damage the crop at all stages of development, both in the field and during post-maturity stage/ storage conditions. Host plant resistance (HPR) has emerged as a critical tool in the sustainable management of insect pests in pigeonpea as a vital legume crop. This review synthesizes key breakthroughs in understanding and applying HPR. It focuses on decades of development and recent advances in identifying resistant/tolerant pigeonpea genotypes and the mechanisms underlying their plant defense for major insect pests. Moreover, emphasis is placed on biochemical, morphological, and genetic traits conferring resistance to significant pests of pigeonpea. In addition, innovations in molecular breeding, genomics, and phenotyping are accelerating the development of pest-resistant genotypes, offering alternatives to chemical control and enhancing crop resilience. In this review, we explored emerging research directions, including multi-omics approaches, gene-editing techniques, and novel breeding techniques, thereby expanding our understanding of host-insect interactions and facilitating precision breeding research. This comprehensive review and opinion underscore the potential of HPR in integrated pest management (IPM) for pigeonpea and highlight future pathways for improving insect pest resistance and ensuring food security in pigeonpea-producing regions across the globe.